Técnicas de modelado y pintura y su incidencia en el desarrollo de la motricidad gruesa en los niños y niñas de 4 a 5 años de la escuela “Dr. Plutarco Naranjo” provincia de Tungurahua año lectivo 2022-2023 - Illicachi Gualli, María Laura (2024)
This study, titled Modeling and Painting Techniques and Their Impact on the Development of Gross Motor Skills in Children Aged 4 to 5 Years at “Dr. Plutarco Naranjo” School, Tungurahua Province, Academic Year 2022-2023, was conducted in an organized and systematic manner. The general objective was to analyze modeling and painting techniques that support the development of gross motor skills. To achieve this, the research employed a quantitative approach, utilizing a quasi-experimental design with documentary, field-based, and cross-sectional methodologies. The study's application level was supported by a deductive theoretical method, which facilitated the creation of an observation sheet consisting of 10 skills to be evaluated, divided into two sections: the first measured the use of modeling and painting techniques, and the second assessed the development of gross motor skills. This instrument was applied to two groups of students: a control group and an experimental group. The experimental group was introduced to the guide Let's Play at Modeling and Painting a Magical World, designed to stimulate gross motor skill development in children aged 4 to 5 years. The findings revealed an average gross motor skill development rate of 22% in the control group, compared to 65% in the experimental group, clearly demonstrating the positive impact of incorporating the guide. Furthermore, statistical verification of the difference in proportions confirmed the hypothesis that modeling and painting techniques significantly contribute to the development of gross motor skills in young children.